2008
DOI: 10.1103/physreva.77.022308
|View full text |Cite
|
Sign up to set email alerts
|

Entanglement distribution in pure-state quantum networks

Abstract: We investigate entanglement distribution in pure-state quantum networks. We consider the case when non-maximally entangled two-qubit pure states are shared by neighboring nodes of the network. For a given pair of nodes, we investigate how to generate the maximal entanglement between them by performing local measurements, assisted by classical communication, on the other nodes. We find optimal measurement protocols for both small and large 1D networks. Quite surprisingly, we prove that Bell measurements are not… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
190
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(196 citation statements)
references
References 32 publications
6
190
0
Order By: Relevance
“…Any pure state can be put into this form via local unitary operations and α can be considered as a measure of the state's entanglement. Apart from basic entanglement percolation other techniques have also been proposed in pure state networks with smaller initial entanglement requirements [11][12][13]15]. These include the global error correction on a square network with no missing edges, as discussed in [21], and it was shown that a lower amount of entanglement was required to succeed at the expense of the final states' fidelity.…”
Section: Tradeoffs Between Different Strategies On Pure State Netmentioning
confidence: 99%
See 2 more Smart Citations
“…Any pure state can be put into this form via local unitary operations and α can be considered as a measure of the state's entanglement. Apart from basic entanglement percolation other techniques have also been proposed in pure state networks with smaller initial entanglement requirements [11][12][13]15]. These include the global error correction on a square network with no missing edges, as discussed in [21], and it was shown that a lower amount of entanglement was required to succeed at the expense of the final states' fidelity.…”
Section: Tradeoffs Between Different Strategies On Pure State Netmentioning
confidence: 99%
“…When this probability exceeds a geometry dependent threshold an infinite cluster is formed of linked nodes. Any two nodes in the cluster can then be transformed into a singlet using the process of entanglement swapping [12,18]. A singlet is generated between nodes with a probability that is independent of their separation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These networks are based on the laws of quantum physics and will offer us new opportunities and phenomena as compared to their classical counterpart. Recently it has been shown that quantum phase transitions may occur in the entanglement properties of quantum networks defined on regular lattices, and that the use of joint strategies may be beneficial, for example, for quantum teleportation between nodes [9,10]. In this work we introduce a simple model of complex quantum networks, a new class of systems that exhibit some totally unexpected properties.…”
mentioning
confidence: 99%
“…Particularly, different nodes in a quantum network are usually connected by multipartite entangled states [3,4], and the twoparty quantum communication protocols between any two possible parities are not set in advance. For accomplishing two-party quantum communications, they need to previously establish bipartite entanglement between them via the help of other parties [5]. It is hence interesting to search efficient ways to extract entangled states with fewer particles (e.g., two particles) from multiparticle entangled states.…”
Section: Introductionmentioning
confidence: 99%